Pengembangan Media Pembelajaran Daring Menggunakan Aplikasi Articulate storyline 3 pada Mata Pelajaran Ekonomi Kelas XI di SMA N 1 Kecamatan Payakumbuh - All Azizah; Nita Sofia; Menik Kurnia Siwi (Jurnal Pendidikan Ekonomi, 2022)
This research aims to 1) expand the number of difficult media available for use in the lax application eloquent narrative in classrooms 3. 2) Consider utilising the articulating narrative app to better understand how media consumers interact in real life. 3) This study's research and development (R&D) approach employs the 4D framework, which stands for Define, Design, Develop, and Disseminate. The study's conclusions focused on media economics and articulating narrative 3app, which instructors and students may use in international commerce and economics lectures. The majority of the instructional resources in this course are derived from the internet and programs that may be run on any computer. Based on the validation results of the following categories: The panel gave the topic a score of 80% (valid), the language a score of 86.6% (very valid), the medium a score of 87.8% (very valid), and the evaluation a score of 84% (very valid). The result, the percentage decreased by 82% between rates (very valid). Student practicality test required a percentage of at least 83.45%, but teacher practicality test required a percentage of at least 88.18% (extremely practical). The result, media learning practices have increased by 85.82% on average (very practical).DOI: https://dx.doi.org/10.17977/UM014v15i22022p144